The mechanical and electrical properties of modified-BNKT lead-free ceramics. Issue 187 (12th February 2018) - Jaita, P.; Manotham, S.; Butnoi, P.; Sanjoom, R.; Arkornsakul, P.; Sweatman, D. R.; Kruea-In, C.; Tunkasiri, T.
ABSTRACT: This research was conducted to study influence of ferric oxide nanoparticles on the properties of modified BNKT ceramics. The optimum sintering temperature was 1125°C at which all compositions had low porosity (0.12–0.19%). Raman and XRD showed coexisting rhombohedral and tetragonal phases throughout the entire compositional range. The Pr, d33 and g33 were slightly degraded when the additive was added. The maximum room temperature dielectric ( ϵ′ = 1689, tan δ = 0.0606) and mechanical properties ( HV = 5.6 GPa, HK = 4.9 GPa, E = 93 GPa and KIC = 1.58 MPa.m 1/2 ) was obtained for the 2 vol% sample.